Glycosaminoglycan-binding properties and kinetic characterization of human heparin cofactor II expressed in Escherichia coli - Sarilla, Suryakala (2010)
Irreversible inactivation of α-thrombin (T) by the serpin, heparin cofactor II (HCII), is accelerated by ternary complex formation with the glycosaminoglycans (GAGs) heparin and dermatan sulfate (DS). Low expression of human HCII in Escherichia coli was optimized by silent mutation of 27 rare codons and five secondary Shine–Dalgarno sequences in the cDNA. The inhibitory activities of recombinant HCII, and native and deglycosylated plasma HCII, and their affinities for heparin and DS were compared. Recombinant and deglycosylated HCII bound heparin with dissociation constants (K(D)) of 6 ± 1 and 7 ± 1 μM, respectively, ~6-fold tighter than plasma HCII, with K(D) 40 ± 4 μM. Binding of recombinant and deglycosylated HCII to DS, both with K(D) 4 ± 1 μM, was ~4-fold tighter than for plasma HCII, with K(D) 15 ± 4 μM. Recombinant HCII, lacking N-glycosylation and tyrosine sulfation, inactivated α-thrombin with a 1:1 stoichiometry, similar to plasma HCII. Second-order rate constants for thrombin inactivation by recombinant and deglycosylated HCII were comparable, at optimal GAG concentrations that were lower than those for plasma HCII, consistent with its weaker GAG binding. This weaker binding may be attributed to interference of the Asn(169) N-glycan with the HCII heparin-binding site.